The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/pharmaceutics12060557
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Colistin Sulfate Dry Powder and Solution for Pulmonary Delivery

Abstract: To assess the difference in the fate of the antibiotic colistin (COLI) after its pulmonary delivery as a powder or a solution, we developed a COLI powder and evaluated the COLI pharmacokinetic properties in rats after pulmonary administration of the powder or the solution. The amorphous COLI powder prepared by spray drying was characterized by a mass median aerodynamic diameter and fine particle fraction of 2.68 ± 0.07 µm and 59.5 ± 5.4%, respectively, when emitted from a Handihaler®. After intratracheal admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“… 31 In contrast, a much higher systemic bioavailability (46 to 64%) have been observed in rat models after intratracheal administration. 35 , 36 The reason for this difference is unclear, but it has been speculated that the diffusion of colistin across the bronchial epithelium is not only mediated by passive diffusion and that specific drug transporters might be implicated in the absorption of colistin – and the expression of these transporters might be different between species. 34 …”
Section: Inhaled Sodium Colistimethatementioning
confidence: 99%
See 3 more Smart Citations
“… 31 In contrast, a much higher systemic bioavailability (46 to 64%) have been observed in rat models after intratracheal administration. 35 , 36 The reason for this difference is unclear, but it has been speculated that the diffusion of colistin across the bronchial epithelium is not only mediated by passive diffusion and that specific drug transporters might be implicated in the absorption of colistin – and the expression of these transporters might be different between species. 34 …”
Section: Inhaled Sodium Colistimethatementioning
confidence: 99%
“…Tewes et al found a lower exposure of the pulmonary epithelial lining fluid to colistin after intratracheal administration of SCM powder to rats, compared to SCM solution. 36 However, they attributed this difference to faster systemic absorption of the drug after the inhalation of powder and, as mentioned above, the PK of SCM absorption might be different in humans. Even using the same formulation, the PK could be different, depending on the delivery system (ie, the design of the nebulizer), although Ratjen et al found no significant differences in sputum colistin concentrations with two different nebulizers.…”
Section: Inhaled Sodium Colistimethatementioning
confidence: 99%
See 2 more Smart Citations
“…Nebulization of high doses of CMS results in high lung tissue colistin concentrations with correspondingly low plasma colistin concentrations (< 2 µg/mL) (Figure 6c) suggesting limited diffusion into the systemic compartment [26,28,41,42,[75][76][77][78][79][80][81][82]. After the initial CMS nebulization of 2 million IU (Figure 8a,b), CMS and colistin plasma concentrations show quite similar pharmacokinetic profiles [79]: an early peak concentration for CMS (30 min), a delayed peak concentration for colistin (3 h) and a slow and progressive decrease in concentrations over the following hours.…”
Section: Pharmacokinetics Of Nebulized Colistimethate Sodiummentioning
confidence: 99%